Post-streptococcal glomerulonephritis associated with atypical hemolytic uremic syndrome: to treat or not to treat with eculizumab? - Kakajiwala, Aadil (Clin Kidney J, 2016)
A 7-year-old male with poststreptococcal glomerulonephritis (PSGN) developed hemolytic uremic syndrome (HUS) and achieved remission. He was treated with eculizumab for 1 year. The eculizumab was discontinued and the patient remained in remission. This is the 10th reported case of PSGN associated with HUS. The histopathological feature observed at the 1-year follow-up was indistinguishable from the expected findings in an individual with healed PSGN without associated HUS. The relatively good prognosis in most prior cases and the absence of any reported recurrences strongly suggest that this form of atypical HUS does not warrant long-term eculizumab therapy.